2016
DOI: 10.1007/s11156-016-0609-6
|View full text |Cite
|
Sign up to set email alerts
|

Explaining co-movements between equity and CDS bid-ask spreads

Abstract: In this paper I show that the co-movements between bid-ask spreads of equities and credit default swaps vary over time and increase over crisis periods. The co-movements are strongly related to systematic risk factors and to the theoretical debt-to-equity hedge ratio. I document that hedging and asymmetric information, besides higher funding costs and market volatility risk, are driving factors of the commonality and are significantly priced in CDS bid-ask spreads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The rise of systemic risk can be also analysed in terms of illiquidity linkages between equity and CDS markets (Marra, 2016): as a matter of fact, when traders are forced to withdraw their positions due to lack of funding or to higher market risk, liquidity decreases in both markets and its cost rises.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of systemic risk can be also analysed in terms of illiquidity linkages between equity and CDS markets (Marra, 2016): as a matter of fact, when traders are forced to withdraw their positions due to lack of funding or to higher market risk, liquidity decreases in both markets and its cost rises.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several studies have indicated that a co-movement exists between these markets (e.g. Marra 2017). Hence, short selling should generally involve re-evaluating assessments of corresponding companies' creditworthiness, which then increases the costs of debt (Glantz 2003;Mock and Sauckel 2010).…”
Section: Hypothesesmentioning
confidence: 99%
“…44 An advantage of our structural credit risk model is that, as a by-product of our estimation, we can compute other firm-level quantities. For example, since we identify both physical and risk-adjusted asset value and volatility dynamics, 42 There is evidence that fixed income markets experienced significant disruptions during this period: Bid-ask spreads were high (Marra (2017)), and the CDS-bond basis diverged and became negative (Bai and Collin-Dufresne (2018)), suggesting that arbitrage activity between markets became more difficult. This may explain the larger pricing errors for our model during this period.…”
Section: Summary Statistics Of Svj Parameter Estimatesmentioning
confidence: 99%
“…There is evidence that fixed income markets experienced significant disruptions during this period: Bid‐ask spreads were high (Marra ()), and the CDS‐bond basis diverged and became negative (Bai and Collin‐Dufresne ()), suggesting that arbitrage activity between markets became more difficult. This may explain the larger pricing errors for our model during this period.…”
mentioning
confidence: 99%